Crime and the transformation of capitalism - Petras, James F. (Crime, law and social change, 1991)
This study investigates factors that enhance criminal behavior. Typically, explanations for increasing crime rates discuss various familial and community attributes; i.e., single parent households and poverty rates. When crime has increased, these attributes are cited as being responsible. This we believe is an incorrect assumption. In particular, we argue the factors that are cited by these authors merely reflect transformations within the greater economic structure. As a result, the familial and community attributes suggested as causing crime are seen as intervening variables; which are either attentuated or amplified in their ability to control criminal behavior by the condition of the economy itself. Within this study, five urban cities (New York, Detroit, Newark, Boston, and Philadelphia) are observed over a twenty eight year period. Structural change is measured by industrial employment and crime is measured by three indices: burglary, robbery and murder. Our investigation reveals a strong relationship between declining industrial employment and increasing crime rates. In addition, we find that the magnitude of this relationship is subject to variation. This variation is dependent upon whether or not the industrial decline experienced was steady or vacilating between high and low levels. These findings support the contention that familial units and other communal organizations are merely intervening variables between large-scale structural changes and criminal behavior. Moreover, it suggests that unless anti-crime efforts (increasing the size of the police forces, increasing state expenditures for law enforcement, etc.) are accompanied by strategies of industrial reorganization, they will have no impact on reducing crime rates.